2014
DOI: 10.5846/stxb201305171102
|View full text |Cite
|
Sign up to set email alerts
|

Habitat assessment of sika deer(Cervus Nippon)in the Taohongling National Nature Reserve in Jiangxi Province, China.

Abstract: The South China subspecies of sika deer (Cervus nippon) has been listed as an endangered species in the IUCN Red Data List, and is also assigned to Protection Class I in the List of Wildlife under Special State Protection as designated by the Chinese State Council. In recent years, sika deer have formed several relatively isolated populations and are distributed in parts of Jiangxi, Zhejiang and Anhui provinces. Taohongling National Nature Reserve is located in Pengze County, Jiangxi Province of China, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Based on OTUs sequences alignment in the NCBI database, the diets of sika deer, Reeve’s muntjac, and Chinese hare includes 203 genera in 90 families, 203 genera in 95 families, and 163 genera in 75 families, respectively ( Editorial Committee of FRPS 2004 ; Jiang 2009 ; see Suppl. material 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on OTUs sequences alignment in the NCBI database, the diets of sika deer, Reeve’s muntjac, and Chinese hare includes 203 genera in 90 families, 203 genera in 95 families, and 163 genera in 75 families, respectively ( Editorial Committee of FRPS 2004 ; Jiang 2009 ; see Suppl. material 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al (2010) found that the sika deer in TNNR mainly eat Homonoia riparia , Fallopia multiflora , Lespedeza bicolor , Pueraria montana , and Vicia faba , and other species, and then especially fed on young leaves and shoots ( Li et al 2014 ). Compared with our study, the dominant forages in the feces of sika deer were Rubus chingii , Loropetalum chinense , Eurya japonica , Camellia japonica , Euonymus grandiflorus , and Phyllostachys edulis in winter; these are all Chinese medicinal herbs, which ensure the prevention of various diseases throughout the life cycle of sika deer ( Yao et al 2010 ; Ye 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…3a, the main activity area of sika deer is the southwestern part of the LNNR; the vegetation form in the area covers deciduous broad-leaved forest, temperate mixed coniferous forest, cold-temperate mixed coniferous forest, and cold-temperate coniferous forest. Comparing to the suitable habitat of sika deer in other distribution areas (Guo 2000;Ma et al 2004;Fu 2006;McCullough et al 2009;Takatsuki 2009;Li et al 2014Li et al , 2015Cheng et al 2020;Yuan et al 2020), these vegetation forms are suitable for sika deer and is widely spread within the natural reserve (Fig. 3a).…”
Section: Spatiotemporal Distribution Of Sika Deermentioning
confidence: 93%
“…There were six subspecies of wild sika deer (Cervus nippon) in China (Guo 2000); three are extant but with limited numbers distributed in Northeast China (Yang et al 2018;Zhou 2018), Northern Sichuan and Southern Gansu provinces (Guo 2000;Cheng et al 2020), Northern Zhejiang Province (Meng & Xu 2003;Yu et al 2006;Cheng et al 2018;Guo et al 2020;Yuan et al 2020), Southern Anhui, the border between Anhui and Jiangsu provinces (Xu et al 1998;Wu et al 2003), and Pengze County in Jiangxi Province (Fu et al 2006;Li 2013;Li et al 2014Li et al , 2015Zhou et al 2019). Because the distribution areas are small and isolated, communication between populations is difficult, and the number of sika deer is decreasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation